Room-temperature operation of Si spin MOSFET with high on/off spin signal ratio. (22nd October 2015) - Tahara, Takayuki; Koike, Hayato; Kameno, Makoto; Sasaki, Tomoyuki; Ando, Yuichiro; Tanaka, Kazuhito; Miwa, Shinji; Suzuki, Yoshishige; Shiraishi, Masashi
Abstract: We experimentally demonstrate a Si spin metal–oxide–semiconductor field-effect transistor (MOSFET) that exhibits a high on/off ratio of source–drain current and spin signals at room temperature. The spin channel is nondegenerate n-type Si, and an effective application of gate voltage in the back-gated structure allows the spin MOSFET operation. This achievement can pave the way for the practical use of the Si spin MOSFET.